Combination of Neoadjuvant Therapy and Liver Transplantation in Pediatric Multisystem Langerhans Cell Histiocytosis With Liver Involvement - Chen, Chen; Gu, Guangxiang; Zhou, Tao; Huang, Mingzhu; Xia, Qiang (Frontiers in Oncology, 2020)
Background Langerhans cell histiocytosis (LCH) is characterized by misguided myeloid differentiation, whose prognosis was poor with involvement of risk organs. Remaining issues include how to improve the outcomes of patients with risk-organ involvement. Methods A retrospective study was conducted in Renji Hospital exploring the effects of neoadjuvant therapy in combination with pediatric liver transplantation (LT) for LCH patients based on data collected between October 2006 and October 2019. Results We presented here five cases of multisystem LCH patients underwent systemic chemotherapy to control active lesions, followed by LT to treat end-stage liver diseases. Manifestations before LT included elevated transaminase levels (n = 5, 100%), jaundice (n = 4, 80%), ascites (n = 3, 60%) and variceal hemorrhage (n = 1, 20%). Three patients underwent orthotopic liver transplantation (OLT) and two underwent living donor liver transplantation (LDLT). Until December 2019, median follow-up time was 32 months (range, 2–67 months). Liver functions significantly improved compared with pre-operative conditions. One patient had perioperative hepatic artery complications and one patient had a recurrence in the lung. EBV infection occurred in four (80%) patients and CMV infection occurred in one (20%). There was one case of drug-induced liver injury diagnosed on biopsy thirteen months after LT. None underwent re-transplantation and there were no rejection or portal vein and biliary complications. Conclusion Combination of neoadjuvant therapy and LT is an effective paradigm in treatment of multisystem LCH with severe liver dysfunction. With advances in chemotherapy regimen for multisystem LCH and LT surgery, perspectives on prognosis for LCH children are promising.